Case Report: Effect of a Retinal Prosthesis System on Charles Bonnet Visual Hallucinations. Issue 12 (December 2020) - Moore, Vincent; Cantin, Sylvie; Carignan, Mathieu; Courchesne, Marie; Qian, Cynthia X.; Poncet, Frédérique
Abstract : SIGNIFICANCE: Charles Bonnet syndrome is commonly encountered and diagnosed in low-vision patients. It can be distressing for some of them, as there is no known effective treatment of this condition. Although there is a growing interest in retinal implants for blind patients with severe retinal diseases, the effect of these devices on Charles Bonnet syndrome visual hallucinations remains undocumented. PURPOSE: The aim of this study was to report changes in the Charles Bonnet syndrome of a patient with retinitis pigmentosa after implantation of the Argus II retinal prosthesis. CASE REPORT: A 65-year-old patient with retinitis pigmentosa and no light perception was frequently experiencing Charles Bonnet syndrome. In the hope of improving his vision, he received an Argus II retinal prosthesis in 2018 and participated in a 10-week rehabilitation program at the Institut Nazareth et Louis-Braille. The nature and the frequency of his Charles Bonnet syndrome were documented with the Questionnaire de repérage du syndrome de Charles Bonnet (a French questionnaire used to screen for Charles Bonnet syndrome) before the surgery and for 70 weeks after it. The patient's visual acuity and visual fields were monitored during the same period. Additional tests were administered to document the visual, psychological, and cognitive states of the patient throughout the study. CONCLUSIONS: Although this case report confirmed that Argus II retinal prosthesis improves the performance of blind patients in visual tests, the improvement was not associated with a decrease in the symptoms of Charles Bonnet syndrome. Abstract : Supplemental digital content is available in the text.